Comparing the performance of Miscanthus x giganteus and wheat straw biomass in sulfuric acid based pretreatment. (March 2015) - Kärcher, M.A.; Iqbal, Y.; Lewandowski, I.; Senn, T.
Highlights: Miscanthus required more energy/acid input in hydrolysis than wheat straw. Combining dilute sulfuric acid and steam explosion resulted in high C5 sugar yield. ADL lignin in miscanthus prevented efficient breakdown of fiber recalcitrance. Abstract: The objective of this study was to assess and compare the suitability of Miscanthus x giganteus and wheat straw biomass in dilute acid catalyzed pretreatment. Miscanthus and wheat straw were treated in a dilute sulfuric acid/steam explosion pretreatment. As a result of combining dilute sulfuric acid- and steam explosion pretreatment the hemicellulose hydrolysis yields (96% in wheat straw and 90% in miscanthus) in both substrates were higher than reported in literature. The combined severity factor (=CSF) for optimal hemicellulose hydrolysis was 1.9 and 1.5 in for miscanthus and wheat straw respectively. Because of the higher CSF value more furfural, furfuryl alcohol, 5-hydroxymethylfurfural and acetic acid was formed in miscanthus than in wheat straw pretreatment.